Proteolytic enzyme models as tunable preclinical platforms for investigating intervertebral disc degeneration - Gewiess, Jan; D’Intino, Annamarie; Santos, Alejandra; Alini, Mauro; Vernengo, Andrea J. (Frontiers in Cell and Developmental Biology, 2026)
Lower back pain (LBP) caused by intervertebral disc (IVD) degeneration is a major global health burden, with significant socioeconomic costs. This review examines proteolytic enzyme-based models for inducing IVD degeneration, focusing on their advantages over mechanical and puncture methods, which often fail to replicate the chronic, multifactorial nature of human degeneration. Enzymatic models, such as chemonucleolysis using chondroitinase ABC (ChABC), chymopapain, collagenase, papain, and trypsin, selectively degrade extracellular matrix components like aggrecan and collagen, mimicking the biochemical and structural changes seen in human IVD degeneration. These models offer controlled, reproducible, and physiologically relevant platforms for studying disease progression and evaluating regenerative therapies. Key findings include the dose- and time-dependent effects of enzymes on disc height loss, biomechanical properties, and matrix composition, as well as their ability to induce mild to moderate degeneration without acute trauma. Comparative studies highlight ChABC’s suitability for early-stage degeneration, while chymopapain and papain produce more severe changes. Enzyme models also provide insights into cellular responses, such as cytokine upregulation and matrix remodeling, which are critical for developing targeted treatments. By enabling precise modulation of degenerative severity, these models hold promise for advancing preclinical research and optimizing regenerative strategies for IVD repair. Looking forward, integrating behavioral and molecular pain outcomes into enzyme-based systems may further enhance their translational value, allowing future models to capture both structural and symptomatic dimensions of disc disease.